Quality of Life and Needs in Caregivers: Results From the Prospective Multicentric Open-Label Randomized Study of Informal Caregivers of Elderly Patients - Astrid Pozet; Astrid Pozet; Sophie Darnis; Magalie Bonnet; Aurélia Meurisse; Aurélia Meurisse; Tienhan Sandrine Dabakuyo-Yonli; Tienhan Sandrine Dabakuyo-Yonli; Catherine Lejeune; Philippe Fagnoni; Philippe Fagnoni; Maryse Gaimard; et al. (Frontiers Media S.A., 2023)
Objectives: To assess health-related quality of life (QoL) in caregivers of elderly patients with chronic disabilities receiving, or not receiving, social worker support.Methods: This multicenter open-label randomized study assigned caregivers to receive an information booklet, exclusively, or with social worker support. Caregivers completed Short Form-36 (SF-36) and Hospital Anxiety Depression Scale quarterly, and Zarit Burden Interview each semester, for 24 months. We reported caregiver QoL mean changes at 12 and 24 months (M12, M24). Longitudinal QoL analysis up to M24 used mixed models for repeated measures (MMRM).Results: Among the 179 caregivers randomized from 2015 to 2019, the SF-36 physical and mental component summary showed no significant changes at M12 and M24, in terms of neither anxiety nor burden. However, depression significantly increased (M12: 1.4 ± 4.0; M24: 1.7 ± 4.1) with significant adjusted mean increase using MMRM at M24: 3.4 [0.6-2.5] in the control group, exclusively.Conclusion: These findings call for better recognition of the social support to prevent caregiver QoL deterioration and alleviate their depression early in the course of the disease.Clinical Trial Registration:ClinicalTrials.gov, identifier NCT02626377.